Environmental protection between chemical practice and applied ethics: a critical review. Issue 9 (20th October 2016) - Moser, Frank; Dondi, Francesco
Abstract : Finding solutions for the struggle to provide food security and access to water are among the most challenging tasks for our century. Chemistry, as one of the principal scientific and technological foundations of modern societies, can provide such solutions. Chemicals play an important role in the efforts of countries to achieve economic growth and their development objectives. Chemicals, however, can have a dual nature. As much as they are vital for ensuring food security and economic growth, their unsound use can adversely affect human health and the environment. This paper critically reviews the changes in the perception of society towards the risks of chemicals. For this, risk reduction strategies are put side by side with the advancements of chemistry as a science. The paper also outlines the underlying ethical consideration of risk assessment methods. As these complex tasks concern as much the field of chemistry as they concern other scientific disciplines, this paper outlines the unique positions of universities to engage such a broad range of different stakeholders involved in these debates. The paper concludes with an evaluation of the role that the higher education organizations can play in integrating these different fields into a single coordinated approach.